2009
DOI: 10.1002/ppap.200900040
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Polymer Coatings to Support Mesenchymal Stem Cell Adhesion, Growth and Differentiation on Variable Stiffness Silicone Elastomers

Abstract: The mechanical properties of the underlying substratum have previously been shown to affect a number of cellular processes including locomotion, proliferation and differentiation. Although polyacrylamide is the most studied variable‐stiffness substrate, silicone elastomers offer a more physiologically relevant range of moduli. Here, we employ plasma polymerisation to apply an acid‐containing polymer thin film to silicone elastomer substrates. This simple one‐step surface modification process renders the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 36 publications
7
46
0
Order By: Relevance
“…The presence of surface acid groups increases the number of oxygencontaining species on the surface, which correlates positively with surface wettability, and in most cases cell adhesion. 36,37 Our study showed, as expected, that cell attachment to uncoated silicone substrates was extremely poor, whereas attachment to the more wettable ppAAc-coated substrate was very good (Fig. 5A, B).…”
Section: Discussionsupporting
confidence: 83%
“…The presence of surface acid groups increases the number of oxygencontaining species on the surface, which correlates positively with surface wettability, and in most cases cell adhesion. 36,37 Our study showed, as expected, that cell attachment to uncoated silicone substrates was extremely poor, whereas attachment to the more wettable ppAAc-coated substrate was very good (Fig. 5A, B).…”
Section: Discussionsupporting
confidence: 83%
“…While hASCs grew in clusters and in a rounded shape on untreated silicone, cells grown on plasma-treated silicone exhibited the characteristic fibroblast-like phenotype. Similar effects were reported by Kim et al [20] for human stomach cancer cells grown on oxygen plasma-treated silicone and by Colley et al [21] for mesenchymal stem cells grown on plasma polymer-coated silicone.…”
Section: Discussionsupporting
confidence: 75%
“…The study of plasma polymer coatings that could potentially be used in biomedical devices is an area of increasing research interest [1][2][3][4][5]. One of the most common classes of thin film treatments employed in biomaterial devices is that of 'low-fouling' or 'stealth' coatings [6].…”
Section: Introductionmentioning
confidence: 99%